A novel lottery protocol for mobile environments. (January 2016) - Chen, Chin-Ling; Chiang, Mao-Lun; Lin, Wei-Chech; Li, De-Kui
Graphical abstract: Structure of our protocol. Highlights: This study proposes a fair and secure protocol allowing users to safely and fairly purchase lottery tickets by smart phone. The proposed lottery protocol can satisfy the fairness, accuracy, and public verification requests in a mobile environment. The proposed protocol can prevent the various malicious attacks discussed above with low computation costs. The proposed protocol can achieve the multi-participants in a mobile environment. Abstract: In general, in order for individuals to take part in a lottery, they must purchase physical lottery tickets from a store. However, due to the popularity and portability of smart phones, this paper proposes a lottery entry purchase protocol for joint multi-participants in a mobile environment. This method integrates cryptology, including elliptic curve cryptography and public key infrastructure, enabling users to safely and fairly join a lottery via a mobile device. The lottery organization involves an untraceable tamperproof decryptor to generate the winning numbers, and the generation of those winning numbers is fair and publicly verifiable. All participants share an equal probability of winning the prize. Subsequently, a comparison table shows that the proposed protocol can withstand attacks and efficiently satisfy the known requirements in a mobile environment. In addition, this study also ensures public verification and mutual authentication.